Effect of COVID-19 Pandemic on Well Child Care and Vaccination - Onimoe, Grace; Angappan, Dhanalakshmi; Chandar, Marie Christianne Ravie; Rikleen, Sarah (Frontiers in Pediatrics, 2022)
ABSTRACT OBJECTIVES The COVID-19 virus is highly contagious primarily via aerosol transmission and has a high mortality rate. On March 13, 2020, the United States declared a national emergency in response to the COVID-19 pandemic. This study aims to enumerate the effect of the pandemic on vaccination rates during the COVID-19 lockdown and the aftermath in pediatric patients aged 6weeks-6 years. STUDY DESIGN A retrospective review of medical records was performed of missed well childcare visits at MetroHealth from March 1, 2020 to June 30, 2020. The sample size of 400 children aged 6 weeks to 6 years were randomly selected. Demographic data, number of calls made to attempt, scheduled WCC, no show rates for clinic appointments, number of missed WCC, location of MH facility, insurance type, vaccination status prior to the pandemic were collected. Statistical analysis was performed with SPSS software (IBM Corp. Released 2020. IBM SPSS Statistics for Windows, Version 27.0. Armonk, NY: IBM Corp). RESULTS From this descriptive study, we found that 43.5% of patients were not up to date on their childhood vaccination. The mean age was 24.38 months (SD 20.15). There were slightly more males (52.8%) in the study than females (47.3%) and most children were of African American descent. More than 50% of patients missed a scheduled well child appointment and 27% had a missed at least two consecutive appointments. CONCLUSION The COVID-19 pandemic has no doubt made a significant mark on health care; the effects would be both immediate and delayed, with vulnerable population being the most impacted. There is an urgent need to prevent a large-scale health disaster of catastrophic potential that could occur if an effective vaccination strategy is not implemented rapidly.